Analyzing the Relationship between Tourism Development and Societal Economic Growth: A Case Study of Alamendah Village, Rancabali District - Putri, Elvina Deninda; Adzilla, Nusaiba; Setiobudi, Akhmad (Institut Teknologi Nasional, Bandung, 2024)
ABSTRACTTourism innovation plays an important role in advancing regional progress, since the tourism sector impact economic growth and income enhancement. Nevertheless, many villages often face challenges, including insufficient community empowerment and knowledge. Therefore, innovation in tourism development is required. This study investigates the correlation between tourism development innovation and the economic growth of the community in Alamendah Village which is measured by community incomes. This study used a mixed method with population research of approximately 23,870 people and a total sample of 100. Data collection involves the distribution of questionnaires and interviews.Keywords: Tourism Innovation, Economic Growth, Correlation.